THE STRATEGIC ROLE OF EMPLOYEE TRAINING IN ENHANCING FRONT-OFFICE JOB PERFORMANCE: EMPIRICAL EVIDENCE FROM A BANKING INSTITUTION - Safril Gazali (INJOSEDU: International Journal of Social and Education, 2025)
Employee training is widely recognized as a strategic human resource development (HRD) intervention that enhances job competence and organizational performance. This study investigates the effect of training on the job performance of front-office employees at BRI Branch Batusangkar, Indonesia. Using a quantitative method, primary data were collected through structured questionnaires and analyzed using regression analysis. The results reveal that training has a significant positive impact on employee performance (β = 0.793, t = 6.992, p < 0.001). The coefficient of determination (R² = 0.556) indicates that training explains 55.60% of the variance in employee performance. These findings support the Human Capital Theory and Ability-Motivation-Opportunity (AMO) framework, suggesting that well-designed training enhances employees' ability and service quality. The study provides theoretical insights and practical recommendations for optimizing HRD strategies in the banking industry.